BADANIA KLINICZNE I DOŚWIADCZALNE W CHOROBACH SERCA, PŁUC I NACZYŃMorphometric investigations of cardiomyocyte mitochondria from children with structural congenital heart malformations - Tosik, Dariusz; Moll, Jacek; Moll, Jadwiga; Kulig, Andrzej; Bartel, Hieronim (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: Abnormal function of the mitochondria, which depends on different factors, is one of the main dysfunctions observed in different types of cardiological illnesses. We present selected parameters of mitochondria obtained during morphometric analysis of cardiomyocytes of children with different types of congenital heart malformations. Aim: Quantitative evaluation of morphological and functional parameters of mitochondria of cardiomyocytes in various types of congenital heart malformations. Material and Methods: Tissue blocks were obtained during surgical correction of three types of heart congenital malformations: ventricular septal defect (VSD), tetralogy of Fallot (TOF) and hypoplastic left heart syndrome (HLHS). The reference group was made up of VSD patients. The age of the patients varied from 11 days to 4 years. Electronograms of mitochondria were analyzed using the image analysis system ImageJ ver. 1.33p. During analysis perimeter and area of mitochondrial profiles, length of the inner membrane and area of the inner compartment were measured. According to this, area of the outer compartment, relative volume of the outer compartment, and ratio of inner compartment volume to inner membrane area were calculated. Results: Obtained results indicate that in the case of cyanotic heart malformations mitochondria are approximately in an orthodox steady state which is characterized by high oxygen consumption and low ATP level. Conclusions: Connection of morphometric parameters with the nature of haemodynamic dysfunctions in the case of non-cyanotic heart malformations indicates that change of the mitochondrial steady-state is a result of both hypoxia and mechanical overloading